Physical and chemical properties of juvenile mahogany according to height level / Muhammad Najmuddin Hashim, Mohd Shakiren Shafian and Mohd Faridzul Mohamed Yusof - Hashim, Muhammad Najmuddin; Shafian, Mohd Shakiren; Mohamed Yusof, Mohd Faridzul (2007)
Juvenile Mahogany was taking from Mr.Zakuan's rubber estate which located at Jengka eight with 32m of height and 14.6cm diameter at breast height. The samples from this tree are used in this research to study about the physical and chemical properties according to the high level for this tree which is density, specific gravity and lignin and ash contents. The method that had used in determination of density is water displacement method. Water immersion method used to determine the Specific Gravity while Alcohol-Benzene solubility and incineration method used to determine the lignin and ash contents respectively. The results from this study for Juvenile Mahogany showed that this tree had 715.147kg/m3 in density, 0.6666 for Specific Gravity and 31.58% and 0.82% for lignin and ash contents respectively. As conclusion, this tree is not suitable for product manufacturing because of its age is not in matured age for that particular purpose.